It's All Logs

Calculus Level 3

Let n n be a positive integer and f ( x ) = x 2 n f(x) = x^{2n} and g ( x ) = log b x g(x) = \log_{b}|x| .

f ( x ) f(x) and g ( x ) g(x) have common tangents at points A A and A A' and the tangent lines intersect at B B forming A A B \triangle{AA'B} as shown above.

If A p A_{p} is the area under the curve f ( x ) = x 2 n f(x) = x^{2n} on the interval [ e 1 2 n , e 1 2 n ] [-e^{\frac{1}{2n}}, e^{\frac{1}{2n}}] , find the value of n n for which A A A B A p = n + 18 \dfrac{A_{\triangle{AA'B}}}{A_{p}} = n + 18 .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 13, 2018

Using the symmetry about the y y axis we have:

f ( x ) = x 2 n f(x) = x^{2n} and g ( x ) = log b ( x ) = ln ( x ) ln ( b ) f ( a ) = 2 n a 2 n 1 = g ( a ) = 1 a ln ( b ) a 2 n = 1 2 n ln ( b ) a = ( 1 2 n ln ( b ) ) 1 2 n g(x) = \log_{b}(x) = \dfrac{\ln(x)}{\ln(b)} \implies f'(a) = 2na^{2n - 1} = g'(a) = \dfrac{1}{a\ln(b)} \implies a^{2n} = \dfrac{1}{2n\ln(b)} \implies a = (\dfrac{1}{2n\ln(b)})^{\frac{1}{2n}}

and

a 2 n = ln ( a ) ln ( b ) 1 2 n ln ( b ) = ln ( 1 2 n ln ( b ) ) 2 n ln ( b ) a^{2n} = \dfrac{\ln(a)}{\ln(b)} \implies \dfrac{1}{2n\ln(b)} = \dfrac{\ln(\dfrac{1}{2n\ln(b)})}{2n\ln(b)}

1 = ln ( 1 2 n ln ( b ) ) \implies 1 = \ln(\dfrac{1}{2n\ln(b)}) \implies 2 n ln ( b ) = 1 e ln ( b ) = 1 2 n e b = e 1 2 n e a = e 1 2 n 2n\ln(b) = \dfrac{1}{e} \implies \ln(b) = \dfrac{1}{2ne} \implies b = e^{\frac{1}{2ne}} \implies a = e^{\frac{1}{2n}} and a 2 n = e a^{2n} = e .

Using A ( e 1 2 n , e ) y e = 2 n e 2 n 1 2 n ( x e 1 2 n ) A(e^{\frac{1}{2n}}, e) \implies \boxed{y - e = 2ne^{\frac{2n - 1}{2n}}(x - e^{\frac{1}{2n}})}

and using symmetry about the y y axis we have A ( e 1 2 n , e ) y e = 2 n e 2 n 1 2 n ( x + e 1 2 n ) A'(-e^{\frac{1}{2n}}, e) \implies \boxed{y - e = -2ne^{\frac{2n - 1}{2n}}(x + e^{\frac{1}{2n}})}

Solving the two equations above we obtain B ( 0 , ( 1 2 n ) e ) B(0,(1 - 2n)e)

Using points A , A , B A, A', B and C ( 0 , e ) C(0,e) we have A A = 2 e 1 2 n AA' = 2e^{\frac{1}{2n}} and B C = 2 n e A A A B = 2 n e 2 n + 1 2 n BC = 2ne \implies A_{\triangle{AA'B}} = 2ne^{\frac{2n + 1}{2n}}

and

A p = e 1 2 n e 1 2 n x 2 n = 2 e 2 n + 1 2 n 2 n + 1 A_{p} = \displaystyle\int_{-e^{\frac{1}{2n}}}^{e^{\frac{1}{2n}}} x^{2n} = \dfrac{2e^{\frac{2n + 1}{2n}}}{2n + 1}

A A A B A p = n ( 2 n + 1 ) = 2 n 2 + n = n + 18 2 ( n 3 ) ( n + 3 ) = 0 \implies \dfrac{A_{\triangle{AA'B}}}{A_{p}} = n(2n + 1) = 2n^2 + n = n + 18 \implies 2(n - 3)(n + 3) = 0 and n 3 n = 3 n \neq -3 \implies n = \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...